The Diversity of Categoricity Without Delay - Kalimullin, I. S. (2017)
We suggest several new ways to compare fully primitive recursive presentations of a structure. Properties of this kind have never been seen in computable structure theory. We prove that these new de nitions are non-equivalent. In this note we give only proof sketches, complete proof will appear in the full version of the paper.